The relationship between job stress and job performance: A case of non-executive employees in Jabatan Kerja Raya (JKR), Kuching Sarawak/ Karmila Suliman - Suliman, Karmila (2016)
This study aimed to investigate the relationship of job stress and job performance among non-executive employees. It was based on the correlational research conducted on 80 of the non-executive employees of public sectors in Jabatan Kerja Raya, Kuching. The data was collected through questionnaires based on close-ended questions. Pearson correlation test was used to determine the relationship between the variables. The results from the data revealed that workload, role conflict, and inadequate monetary reward were the factors causing job stress in employees’ job performance. Thus, it was recommended that the manager should minimize stress by lowering the workload, provide clear definition of what is expected from the employees, pay adequate salary and provide counseling to the employees in order to improve their job performance.